"True" Cumulative Incidence of and Risk Factors for Hip Dislocation within 2 Years After Primary Total Hip Arthroplasty Due to Osteoarthritis: A Nationwide Population-Based Study from the Danish Hip Arthroplasty Register. (17th February 2021) - Hermansen, Lars L.; Viberg, Bjarke; Hansen, Lars; Overgaard, Soeren
Abstract : Background: Hip dislocation is one of the leading indications for revision of total hip arthroplasty (THA) implants, and the extent of this complication is often measured by the number of revisions. The exact incidence of dislocation can be difficult to establish as closed reductions may not be captured in available registers. The purpose of this study was to identify the "true" cumulative incidence of hip dislocation (revisions and closed reductions) after primary THA, and the secondary aim was to identify risk factors for dislocation. Methods: From the Danish Hip Arthroplasty Register, we identified 31, 105 primary THAs indicated by primary osteoarthritis that had been performed from 2010 to 2014 and had 2 years of follow-up. Dislocations were identified through extraction from the Danish National Patient Register. Matching diagnosis and procedure codes were deemed correct while non-matching codes were reviewed through a comprehensive, nationwide review of patient files. Risk factors were analyzed with multiple logistic regression analysis and presented as odds ratios (ORs) with 95% confidence intervals (CIs). Results: Our review of patient files identified 1, 861 dislocations in 1, 079 THAs, which corresponds to a 2-year cumulative incidence of 3.5% (CI = 3.3% to 3.7%). This was a 50% increase compared with the correctly coded dislocations captured by administrative register data only. Patients who were <65 years of age had a lower dislocation risk (OR = 0.70; CI = 0.59 to 0.83) and those who were >75 years of age had a higher risk (OR = 1.32; CI = 1.14 to 1.52) compared with those who were 65 to 75. Male sex (OR = 0.86; CI = 0.75 to 0.98), cemented fixation (OR = 0.71; CI = 0.58 to 0.87), and lateral approach (OR = 0.28; CI = 0.16 to 0.49) were all associated with a lower risk. A head size of 32 mm was associated with a higher risk of dislocation (OR = 1.27; CI = 1.10 to 1.46) than 36-mm heads, whereas dual-mobility cups had a reduced risk (OR = 0.13; CI = 0.05 to 0.36). Conclusions: We found the "true" cumulative incidence of dislocations within 2 years after primary THAs performed between 2010 and 2014 in Denmark to be 3.5%. Age, sex, American Society of Anesthesiologists (ASA) score, head size and type, fixation method, and surgical approach were independent significant factors for dislocation. Comprehensive search algorithms are needed in order to identify all dislocations so that this complication can be accurately reported in national registers.